Burnout - detection and prevention : burnout in upper secondary-level schools in Iceland - Sigrún María Ammendrup 1975- (2020)
This research has two different motivations, even though it is focusing on the same topic, burnout. One part aims at exploring whether teachers in upper secondary-level schools are happy in their work or whether they are showing any signs of burnout or are considering changing their profession. The other part focuses on whether schools in the upper secondary-level have any specific plans when welcoming back teachers to work after burnout. The quantitative research method of sending out questionnaires was used for both parts of this research. CBI or Copenhagen Burnout Inventory was used to measure burnout for teachers, and the questions from the study of Veitch et al. was used to measure work satisfaction and turnover intentions. The questionnaire for managers focused on getting information on whether there was a specific plan for welcoming teachers back. Schools do not seem to have a specific plan for welcoming employees back after burnout, but there are some available resources that they can use to help teachers to come back to work after a long-term sickness. Teachers showed some sign of burnout in all three dimensions of burnout as defined by CBI, or personal burnout, job-related burnout and client/student-related burnout. For individual burnout teachers had 6,9 points, for job-related burnout eight and client-related burnout 6,2. Women seem to show more signs of burnout than men. Due to the small sample size for both questionnaires sent out, it is not easy to generalise from the results of this study. Still, hopefully, the results are of some importance to the profession as well as supporting upper secondary-level school managers to prevent occupational burnout and burnout within their faculty.